Risk, uncertainty and the theory of planned behavior: a tourism example - Quintal, Vanessa; Lee, J.; Soutar, G. (Elsevier Science Ltd, 2010)
The differential impacts risk and uncertainty have on travel decision-making were explored by examining the constructs' influence on the antecedents of intentions to visit Australia using the theory of planned behavior. Respondents were obtained from online consumer panels in South Korea, China and Japan. The South Korean and Chinese samples were general population samples, while the sample from Japan was an international travelers' sample. The extended model fitted the data well, explaining between 21 and 44 percent of the variance in intentions. Subjective norms and perceived behavioral control significantly impacted on intentions in all country samples, whereas attitudes toward visiting Australia were only significant in Japan. Subjective norms influenced attitudes and perceived behavioral control in all country samples. Finally, perceived risk influenced attitudes toward visiting Australia in South Korea and Japan, while perceived uncertainty influenced attitudes toward visiting Australia in South Korea and China and perceived behavioral control in China and Japan.